Ro 15-4513 Antagonizes Alcohol-Induced Sedation in Mice Through αβγ2-type GABAA Receptors - Linden, Anni-Maija; Schmitt, Ulrich; Leppä, Elli; Wulff, Peer; Wisden, William; Lüddens, Hartmut; Korpi, Esa R. (Frontiers in Neuroscience, 2011)
Ethyl alcohol (ethanol) has many molecular targets in the nervous system, its potency at these sites being low compared with those of sedative drugs. This has made it difficult to discover ethanol’s binding site(s). There are two putative binding sites at gamma-aminobutyric acid (GABA) type A receptor subtypes for the proposed ethanol antagonist Ro 15-4513, the established gamma2 subunit-dependent benzodiazepine site and the recently reported delta subunit-dependent Ro 15-4513/ethanol binding site. Here, we aimed at clarifying the in vivo role of Ro 15-4513 at these two sites. We found that the antagonism of ethanol actions by Ro 15-4513 in wildtype mice was dependent on the test: an open field test showed that light sedation induced by 1.5-1.8 g/kg ethanol was sensitive to Ro 15-4513, whereas several tests for ethanol-induced anxiolytic effects showed that the ethanol-induced effects were insensitive to Ro 15-4513. Antagonism of ethanol-induced sedation by Ro 15-4513 was unaffected in GABAA receptor delta subunit knockout mice. By contrast, when testing the GABAA receptor gamma2 subunit F77I knock-in mouse line (gamma2I77 mice) with its strongly reduced affinity of the benzodiazepine sites for Ro 15-4513, we found that the ethanol-induced sedation was no longer antagonized by Ro 15-4513. Indeed, gamma2I77 mice had only a small proportion of high-affinity binding of [3H]Ro 15-4513 left as compared to wildtype mice, especially in the caudate-putamen and septal areas, but these residual sites are apparently not involved in ethanol antagonism. In conclusion, we found that Ro 15-4513 abolished the sedative effect of ethanol by an action on gamma2 subunit-dependent benzodiazepine sites.